2022
DOI: 10.1007/s40199-021-00430-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of tocilizumab with corticosteroid therapy in treating COVID-19 patients: a systematic review and meta-analysis

Abstract: Purpose Tocilizumab has shown equivocal outcomes in reducing mortality in COVID-19. The corticosteroids appear to be an affordable alternative to tocilizumab. This study aims to estimate the efficacy of tocilizumab and the corticosteroids particularly dexamethasone and methylprednisolone and to identify possible determinants of their efficacy. Methods Five electronic databases were searched for studies involving tocilizumab, dexamethasone, and methylprednisolone in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
0
12
0
3
Order By: Relevance
“…Mikulska et al was an early study that provided a hint of the favorable outcome of the combined therapy of steroids with tocilizumab, in which the methylprednisolone + tocilizumab treatment arm demonstrated a superior outcome in averting death and intubation compared to single therapy arms [ 28 ]. A recently published systematic review and meta-analysis by Lim et al showed that the concurrent use of a corticosteroid such as methylprednisolone was a significant influencer of tocilizumab efficacy in reducing mortality and improving survival [ 29 ]. This is especially visible in the excellent outcomes demonstrated by the CHIC study, which used 3–6 days of methylprednisolone in combination with tocilizumab in the late stages of the disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mikulska et al was an early study that provided a hint of the favorable outcome of the combined therapy of steroids with tocilizumab, in which the methylprednisolone + tocilizumab treatment arm demonstrated a superior outcome in averting death and intubation compared to single therapy arms [ 28 ]. A recently published systematic review and meta-analysis by Lim et al showed that the concurrent use of a corticosteroid such as methylprednisolone was a significant influencer of tocilizumab efficacy in reducing mortality and improving survival [ 29 ]. This is especially visible in the excellent outcomes demonstrated by the CHIC study, which used 3–6 days of methylprednisolone in combination with tocilizumab in the late stages of the disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stone and colleagues’ [ 96 ] double-blinded study failed to detect the benefit or harm of the use of Tocilizumab in COVID-19 patients, which is not part of our study to analyze the impact of Tocilizumab specifically on patient outcomes. On the other hand, Lim et al [ 97 ] showed that a combination of Tocilizumab and Dexamethasone is effective in reducing mortality in severe COVID-19 infections where single therapy fails. However, the study of Lim et al [ 97 ] did not include the effect of diabetes in COVID-19 management with Tocilizumab and Dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Lim et al [ 97 ] showed that a combination of Tocilizumab and Dexamethasone is effective in reducing mortality in severe COVID-19 infections where single therapy fails. However, the study of Lim et al [ 97 ] did not include the effect of diabetes in COVID-19 management with Tocilizumab and Dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…The Randomised Evaluation of COVID-19 Therapy (RECOVERY) trial is an adaptive platform trial assessing multiple interventions for patients hospitalized with COVID-19 in the UK. The trial began in early 2020 and has identified several effective (dexamethasone, tocilizumab and casirivimab/imdevimab) and six ineffective treatments [102][103][104]. This is a remarkable achievement in 2 years and illustrates the potential of platform trials to rapidly produce high-quality data and adapt to new medications as they become available.…”
Section: Novel Trial Designsmentioning
confidence: 99%